DOCUMENTATION OF LUTHERAN CHURCH IN KLAIPĖDA REGION IN THE 17TH CENTURY - JURGEN ARNAŠIUS (ARNASZUS), HELMUT HANS (Knygotyra, 2012)
Klaipėdos universiteto Literatūros katedra Manto g. 84, LT-92294 Klaipėda El. paštas: helmutarnaszus@gmail.com